Iminoxyl Radical‐Based Strategy for Intermolecular CO Bond Formation: Cross‐Dehydrogenative Coupling of 1, 3‐Dicarbonyl Compounds with Oximes. Issue 10 (20th June 2014) - Krylov, Igor B.; Terent'ev, Alexander O.; Timofeev, Vladimir P.; Shelimov, Boris N.; Novikov, Roman A.; Merkulova, Valentina M.; Nikishin, Gennady I.
Abstract Cross‐dehydrogenative CO coupling of 1, 3‐diketones and 1, 3‐keto esters with oximes was realized for the first time. The reaction proceeds in the presence of the oxidants [KMnO4, Mn(OAc)2/KMnO4, Mn(OAc)3⋅2 H2O, MnO2, Mn(acac)3, Fe(ClO4)3, Cu(ClO4)2⋅6 H2O, Cu(NO3)2⋅2.5 H2O, and (NH4)2Ce(NO3)6]. Twenty cross‐coupling products were synthesized using potassium permanganate (KMnO4), manganese(II) acetate dihydrate [Mn(OAc)3⋅2 H2O], or the manganese(II) acetate/potassium permanganate [Mn(OAc)2/KMnO4] system; yields are 27–92%. The synthesis can be easily scaled up to gram quantities of the target products. Apparently, the reaction proceeds via a radical mechanism in which the oxidizing agent serves to generate radicals from oximes and perform the one‐electron oxidation of 1, 3‐dicarbonyl compounds. The formation of oxime radicals was confirmed quantitatively by electron spin resonance (ESR) spectroscopy. The coupling described in the present study is the first example of the selective intermolecular reaction involving unstable iminoxyl radicals generated in situ. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>